PAA-templated CuO nanoparticles : synthesis and self-assembly - Li, Zhenggang. (2009)
Molecular self-assembly is a strategy for nanofabrication that involves designing molecules and supramolecular entities so that shape-complementarity causes them to aggregate into desired structures. In this report, we put efforts in studying the self assembly of CuO nanopartilces. With Cu(NO3)2•3H2O and NaBH4 as the starting materials, CuO nanoparticles have been successfully synthesized through sequential reduction and oxidation of copper species. Poly (acrylic acid) (PAA), plays an important role in the self-assembly process of CuO nanoparticles. By modifying the presence of PAA, CuO nanoparticles with disk-like, leaf-like and flower-like shapes are obtained. The optical properties of above mentioned CuO nanostructures are studied through UV-vis absorption spectra. In addition, the effect of PAA ligand during CuO synthesis process and postsynthesis modification is investigated. It is found that PAA not only serves as surface protection ligand, but also acts as linkage between primary CuO nanoparticles and facilitate them to self organize into different shapes. Lastly, the formation mechanism of PAA-templated CuO nanostructures is proposed based on experimental observations.